2020
DOI: 10.1002/vzj2.20058
|View full text |Cite
|
Sign up to set email alerts
|

Crop growth and soil water fluxes at erosion‐affected arable sites: Using weighing lysimeter data for model intercomparison

Abstract: Agroecosystem models need to reliably simulate all biophysical processes that control crop growth, particularly the soil water fluxes and nutrient dynamics. As a result of the erosion history, truncated and colluvial soil profiles coexist in arable fields. The erosion-affected field-scale soil spatial heterogeneity may limit agroecosystem model predictions. The objective was to identify the variation in the importance of soil properties and soil profile modifications in agroecosystem models for both agronomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 86 publications
2
29
0
Order By: Relevance
“…In the recent comparison of the performances of 12 models made by Groh et al. (2020), models that used Richards‐based methods achieved better results in terms of SWC and net water flux at the lysimeter bottom than models that did not integrate them. Moreover, this study further validated our methodology by emphasizing the importance of lysimeters for providing the necessary soil‐related data for testing soil–vegetation–atmospheric models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent comparison of the performances of 12 models made by Groh et al. (2020), models that used Richards‐based methods achieved better results in terms of SWC and net water flux at the lysimeter bottom than models that did not integrate them. Moreover, this study further validated our methodology by emphasizing the importance of lysimeters for providing the necessary soil‐related data for testing soil–vegetation–atmospheric models.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shelia et al (2018) reported that integrating the HYDRUS-1D model into DSSAT provided better SWCs compared with the tipping bucket method, despite the appearance of submodel discrepancies from crop variables. In the recent comparison of the performances of 12 models made by Groh et al (2020), models that used Richards-based methods achieved better results in terms of SWC and net water flux at the lysimeter bottom than models that did not integrate them. Moreover, this study further validated our methodology by emphasizing the importance of lysimeters for providing the necessary soil-related data for testing soil-vegetationatmospheric models.…”
Section: Discussionmentioning
confidence: 99%
“…The winter wheat module used builds on the default winter wheat parameterization in DAISY, which has been used in several articles, providing good correspondence between measured and simulated values of biomass production and N dynamics (Abrahamsen and Hansen, 2000), crop production, soil water fluxes and nutrient dynamics (Hansen et al, 1990;Diekkrüger et al, 1995;Groh et al, 2020), and yield estimates (Palosuo et al, 2011;Ozturk et al, 2017). A new parametrization of winter wheat was recently presented by Gyldengren et al (2020), based on recent experimental data from Eastern Denmark.…”
Section: Model Simulationmentioning
confidence: 99%
“…A major shortcoming that limits the validity of agroecosystem models is not accurately capturing this heterogeneity Vrugt et al, 2003). Groh et al (2020) investigate the response of different agroecosystem models to a range of different soil profiles and input information. Above-and belowground processes are simulated for soils representing heterogeneity in a typical hummocky agricultural landscape with growing crops.…”
Section: Core Ideasmentioning
confidence: 99%